Effect of anisotropic diffusion on spinodal decomposition. Issue 6 (7th December 2018) - Vuijk, Hidde Derk; Brader, Joseph Michael; Sharma, Abhinav
Abstract : Phase transition dynamics of a fluid system are very sensitive to the diffusion tensor. Abstract : We study the phase transition dynamics of a fluid system in which the particles diffuse anisotropically in space. The motivation to study such a situation is provided by systems of interacting magnetic colloidal particles subject to the Lorentz force. The Smoluchowski equation for the many-particle probability distribution then acquires an anisotropic diffusion tensor. We show that in comparison to the isotropic case, anisotropic diffusion results in qualitatively different dynamics of spinodal decomposition. Using the method of dynamical density functional theory, we predict that the intermediate-stage decomposition dynamics are slowed down significantly by anisotropy; the coupling between different Fourier modes is strongly reduced. Numerical calculations are performed for a model (Yukawa) fluid that exhibits gas–liquid phase separation.